PODCASTING AS A MODERN DA’WAH TOOL FOR CONVEYING SIRAH NABAWIYAH - Nazih, Abdullah Ghulam; Hidayatullah, Hidayatullah; Uyuni, Badrah (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
The rapid advancement of digital media has revolutionized the methods of delivering Islamic teachings, particularly in the realm of da’wah. Podcasts, as a versatile and accessible digital medium, have become increasingly popular for disseminating religious knowledge. This research explores the development and utilization of podcasts as a means for conveying Sirah Nabawiyah (the biography of Prophet Muhammad) through the "Basyiroh Podcast" by the Indonesia Siroh Institute. The study employs a qualitative approach, focusing on content development, production challenges, and the effectiveness of podcasting as a da’wah tool. Through an analysis of the production process and audience engagement, the study highlights the integration of educational and entertaining elements in the podcast's format, making it accessible to diverse audiences, including housewives and the younger generation. Findings indicate that the podcast has successfully leveraged the YouTube platform to engage listeners with high-quality content, balancing the complexities of media production with the need for accurate Islamic teachings. Furthermore, this research emphasizes the challenges faced in maintaining content accuracy, technical production standards, and team coordination. The Basyiroh Podcast, by enhancing accessibility and interactivity, contributes significantly to modern da’wah practices. The study concludes with recommendations for further exploring the impact of digital media in da’wah and the potential of podcasts to reach broader audiences in the digital age.